Direct evidence on occurrence of emerging liquid crystal monomers in human serum from E-waste dismantling workers: Implication for intake assessment. (November 2022) - Li, Yuhe; Zhang, Tao; Cheng, Zhipeng; Zhang, Qianru; Yang, Ming; Zhao, Leicheng; Zhang, Shaohan; Lu, Yuan; Sun, Hongwen; Wang, Lei
Graphical abstract: Highlights: The occurrence of LCMs in the serum samples of e-waste occupational workers was observed. Fluorinated LCMs were found as dominant LCMs in the serum samples. LCMs serum levels were comparable to other e-waste related organic chemicals. Human daily intake of LCMs to occupational workers were firstly assessed based on internal exposure approach. Abstract: Liquid crystal monomers (LCMs) are widely used chemicals and ubiquitous emerging organic pollutants in the environment, some of which have persistent, bio-accumulative, and toxic potentials. Elevated levels of LCMs have been found in the e-waste dismantling associated areas. However, information on their internal exposure bio-monitoring is scarce. For the first time, occurrences of LCMs were observed in the serum samples of occupational workers (n = 85) from an e-waste dismantling area in South China. Twenty-nine LCMs were detected in serum samples of the workers, with a median value of 35.2 ng/mL (range: 7.78–276 ng/mL). Eight noticed LCMs were found to have relatively high detection frequencies ranging from 52.9% to 96.5%. The correlation analysis of individual LCMs indicated potential common applications and similar sources to the LCMs in occupational workers. Fluorinated LCMs were identified as the predominant monomers in the workers. Additionally, the estimated daily intake of the LCMs in the occupational workers was significantly higher than those in residents from the reference areas ( p < 0.05, Mann-Whitney U Test, median values: 1.46 ng/kg bw/day versus 0.40 ng/kg bw/day), indicating a substantially higher exposure level to e-waste dismantling workers.